Absorption coefficient and transmission loss measurement of a local materials ; The refinement of Bahasa Malaysia phonetically balanced word lists ; Acoustics modelling of Shah Alam mosque and its optimum sound system ; Timing recovery for bit error rate measurement ; Kajian sifat corak texture / [mikrofilem] - Abdul Aziz Suboh; Aini Sulaiman; Azawana Abd. Jalil; Lau, Bik Soon; Sutarwan Wejo (Kuala Lumpur : UTM, 1994)
Project paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1994